TRANSFORMATION OF POLITICAL DISCOURSE IN THE CONTEXT OF MEDIATIZATION: CHALLENGES FOR SOCIAL ORDER IN UKRAINE - Руслан ВЕЛИЧКОВСЬКИЙ (Епістемологічні дослідження у філософії, соціальних і політичних науках)
Research objective: To analyze the transformation of political discourse under mediatization conditions and its impact on social order in Ukrainian society. The study employs a comprehensive application of systemic approach, institutional, comparative and historical methods, as well as content analysis of official social media pages of state institutions. The dualistic nature of modern mediatization is established, which manifests through simultaneous processes of media integration into traditional social institutions and the formation of media as an independent social institution. Key challenges to social order arising from the mediatization of political discourse are identified. A conceptual model of interaction between media and political institutions in the context of social order transformation is proposed. The research reveals the emergence of new forms of political engagement and participation facilitated by digital platforms. It demonstrates how social media has become a crucial arena for political discourse, reshaping power dynamics between political actors and citizens. The study also highlights the potential risks of information manipulation and the spread of misinformation in the mediatized political environment. The understanding of mechanisms of political actors’ adaptation to media requirements and transformation of traditional forms of political communication is expanded. The research results can be used to develop communication strategies for state institutions under mediatization conditions. For the first time, a comprehensive analysis of the impact of political discourse mediatization on social order in the Ukrainian context is conducted, taking into account the specifics of hybrid threats. An in-depth study of the influence of digital technologies and social networks on the transformation of political communication in the context of hybrid threats is suggested. The article is empirical in nature.